Contemporary Review of Minimally Invasive Mitral Valve Surgery: Current Considerations and Innovations - Sharifa Alsheebani; Daniel Goubran; Benoit de Varennes; Vincent Chan (Journal of Cardiovascular Development and Disease)
Minimally invasive mitral valve surgery (MIMVS) has become a well-established alternative to traditional median sternotomy at high-volume surgical centers. Advancements in surgical instruments have led to further refinement of MIMVS. However, MIMVS remains limited to select patients in select settings. In this review, we provide a brief overview of the evolution of MIMVS, as well as a technical description of the most relevant aspects of minimally invasive mitral valve surgery.